(3ChVM GdeGSdc Edi CdajI GHf eGdcs - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEf cJGH GdNdGUI GdCdajI aj Yde GdYQHjI fXe GdEeGe GdYdGeI LeGd GdOjf CHj YHO Gddg eMeO Hf eGdc GdWGFj QMeg Gddg cJGH UZQ MLeG ZRQ YdeG ZjQ Cfg dEaQGW GdEjLGR bO cGf jYO ef GdCdZGR (B...s
(3BNQgG (B:s
... (3hNQL HbhdfG TGFYG fMh bhdge aj oCUjdGd JUZjQ CUjd Ydi ZjQ bjGS haj GVWLY haj fMh Ydj aj Gdhba CUjdGd ???s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\147s
(3cTa GdXfhf (B1\152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs